2002
DOI: 10.1165/ajrcmb.26.2.4673
|View full text |Cite
|
Sign up to set email alerts
|

The Presence of Simian-Virus 40 Sequences in Mesothelioma and Mesothelial Cells Is Associated with High Levels of Vascular Endothelial Growth Factor

Abstract: The aim of this study was to evaluate whether the presence of simian virus-40 (SV40) is associated with increased release of vascular endothelial growth factor (VEGF) in human malignant mesothelioma (MM) cells. We studied nine cell lines derived from pleural effusion (PE) of patients with MM, and three different cultures of normal human mesothelial cells (NHMC) derived from pleural fluid of patients with congestive heart failure. NHMC were transfected with full length SV40 (NHMC-FL) or large T antigen (NHMC Ta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 66 publications
(35 citation statements)
references
References 25 publications
0
35
0
Order By: Relevance
“…We next stimulated HMC and SV40-negative MMB cells with HGF and VEGF, which have been reported to be induced by SV40 in malignant mesothelioma cells (12,15,20). These growth factors elicited Akt and Erk1/2 activities in HMC and SV40-negative MMB cells (Fig.…”
Section: Resultsmentioning
confidence: 90%
See 1 more Smart Citation
“…We next stimulated HMC and SV40-negative MMB cells with HGF and VEGF, which have been reported to be induced by SV40 in malignant mesothelioma cells (12,15,20). These growth factors elicited Akt and Erk1/2 activities in HMC and SV40-negative MMB cells (Fig.…”
Section: Resultsmentioning
confidence: 90%
“…Interestingly, microarray analysis revealed that expression of Met, among other genes, is associated with asbestos exposure in mesothelial cells (13) and several other growth factors are released by SV40-positive HMC and malignant mesothelioma cells, including insulin-like growth factor-I (IGF-I) and vascular endothelial growth factor (VEGF; refs. 14,15).…”
Section: Introductionmentioning
confidence: 99%
“…This effect may represent an important oncogenic mechanism and, once chromosomal alterations are fixed in the host cells, viral sequences may be dispensable for the maintenance of transformation and may be lost by the neoplastic tissues. It is possible therefore that, while continuous expression of BKV Tag is necessary for maintenance of BKV transformation in rodent cells, in human cells the transformed phenotype is maintained by mechanisms Tag induces production and release of hepatocyte growth factor and vascular endothelial growth factor (Cacciotti et al, 2001(Cacciotti et al, , 2002Catalano et al, 2002). The role of Tag in these functions was demonstrated by reversion of the neoplastic phenotype of mesothelioma cell lines after transfection and expression of an antisense SV40 Tag RNA (Waheed et al, 1999).…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 99%
“…open pleural biopsy (VATS, mini-thoracotomy) or not. Among these biomarkers, insulin growth factor, hepatocyte growth factor and Simian Virus-40 have been proven to play an important role in the development and progression of malignant mesothelioma [7][8][9]. Likewise, a recent study has shown that plasma N/CD-13 activity had a strong correlation with tumor load in malignant pleural diseases [10].…”
Section: Discussionmentioning
confidence: 99%